Navigating Award‐Winning Nonfiction Children's Literature. (3rd April 2019) - Smith, Jennifer M.; Robertson, Marla K.
Abstract: Nonfiction children's literature has changed in recent years, including an increase in organizational, design, and text features. The authors conducted a content analysis of 112 nonfiction award‐winning and honor books from 2000 to 2018 to examine how the books have changed over time. The authors discuss the patterns, changes, and complexities found in nonfiction children's literature and provide text sets and guiding questions for classroom instruction and exploration of three features that appear in books in a variety of ways and may be challenging for students: atypical text, graphics with information, and supplemental expository information.